ANALYSIS OF THE CAUSALITY RELATIONSHIP BETWEEN SPENDING ON HIGHER EDUCATION AND SOME ECONOMIC VARIABLES IN IRAQ FOR THE PERIOD 1990-2020 - Isra S. K. Al-Ribhawee (Scholar Express Journals, 2022)
Higher education is important because it creates and develops human capital and provides qualified human cadres, which requires restructuring government spending so that an increase in funding allocated to education is brought about. During the period 1990-2020, government spending was weak on educational institutions in Iraq, which led to a decline in The role of these institutions in the economic development of the country. The highest percentage of spending on higher education of GDP was 0.47% in 2007 and the lowest was 0.01% in 2005. The number of public universities reached 35, and the number of private universities and colleges reached 64 universities and private colleges in 2020. This was accompanied by an increase in the number of students and a weakening of the absorptive capacity of public universities. Iraq is considered one of the countries most affected by the Corona virus pandemic in the Middle East, in terms of the rate of injuries and deaths, and as a result of the pandemic, education has been transformed to lectronic learning platforms. Granger causality also showed the existence of a significant causal relationship between government spending on higher education, gross domestic product, the number of graduate students, and unemployment.
Keywords: : higher education spending; Granger causality; unemployment; economic